PERAN GURU PENDIDIKAN AGAMA ISLAM DALAM MENCEGAH BULLYING DI SEKOLAH - Yusniar, Yusniar; Irmayani, Irmayani; Saiful, Saiful (NIHAYAH: Journal of Islamic Studies, 2025)
The prevalence of bullying cases in schools should be a primary concern for educational administrators and school authorities to address promptly in order to protect students. Bullying prevention in schools must be undertaken by all school members, including PAI teachers. This study indicates that PAI teachers play an active role in combating bullying through a unique approach, namely becoming friends to their students. PAI teachers are open to students, always ready to listen to their complaints, act as advisors, and help solve students' problems. This research falls into the category of qualitative research with a descriptive approach and collects both primary and secondary data. The research findings show that bullying behavior often starts from teasing games, calling parents' names, or bothering friends, which can then escalate into fights. Therefore, the role of PAI teachers in preventing bullying is not just as instructors but also as educators who give extra attention to students, teach the meaning of unity and brotherhood, encourage living with mutual care, do not differentiate between students, and often assign group tasks so that students get to know each other better.